Integrated Dynamical Model for Malaysian Solid Waste Management Using System Dynamics - Zulkipli, Faridah; Mohd Nopiah, Zulkifli; Ezlin Ahamad Basri, Noor; Jack Kie, Cheng; Zulkepli, Jafri; Irwan Khalid, Khairul (International Journal of Engineering and Technology, 2018)
Solid waste management is considered as one of the complex and dynamics problems worldwide due to rapid population, changing life style, urbanization process towards sustainable development and uncontrollable increment in solid waste generation. An efficient performance of solid waste management is depending on systematic strategic planning. The aim of this paper is to develop an integrated dynamical model to simulate the complexity of solid waste management in Malaysia. System dynamics as one of optimization methodology is applied in order to illustrate the continuous process in solid waste management Malaysia. As a result, an increasing trend of solid waste generation over time. By 2025, it is forecasted that total waste will be more than 15 million tonnes. Based on developed proposed model, the main factor to solid waste generation is population. However, in order to reduce the total solid waste, we cannot simply reduce the population Therefore; further actions are needed in order to reduce the total solid waste generation. The proposed model is capable of assisting the decision maker to determine the effectiveness of solid waste management practices especially in strategies planning and system design improvement.Â Â